2019
DOI: 10.1038/s41598-019-40046-2
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp cell-derived powerful inducer of TNF-α comprises PKR containing stress granule rich microvesicles

Abstract: It is well known that dental pulp tissue can evoke some of the most severe acute inflammation observed in the human body. We found that dental pulp cells secrete a factor that induces tumor necrosis factor-α production from macrophages, and designated this factor, dental pulp cell-derived powerful inducer of TNF-α (DPIT). DPIT was induced in dental pulp cells and transported to recipient cells via microvesicles. Treatment of dental pulp cells with a PKR inhibitor markedly suppressed DPIT activity, and weak int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…AHNAK1 is highly sensitive to metal-dependent proteases [ 91 ] and calcium-dependent proteolysis leads to the cleavage of AHNAK1 at specific sites on N- and C- terminal domains [ 92 ]. AHNAK1 contained in purified EVs migrates as a set of shorter peptides compared to the full length AHNAK1, supporting the hypothesis that AHNAK1 proteolysis accompanies vesicle formation (this evidence is supported by comparing Figure 10 panel c and panel f in [ 93 ] and in Figure 7a of [ 94 ]). Such a scenario is further supported by the finding that targeting the C-terminal domain of AHNAK1 (residues 5645–5673) to the membrane bound annexin2/S100A10 complex, in place of the full length AHNAK1, was sufficient to cause membrane blebbing that evolves into vesicular structures ( Figure 4 ).…”
Section: S100b Secretion By Adipocytesupporting
confidence: 63%
See 1 more Smart Citation
“…AHNAK1 is highly sensitive to metal-dependent proteases [ 91 ] and calcium-dependent proteolysis leads to the cleavage of AHNAK1 at specific sites on N- and C- terminal domains [ 92 ]. AHNAK1 contained in purified EVs migrates as a set of shorter peptides compared to the full length AHNAK1, supporting the hypothesis that AHNAK1 proteolysis accompanies vesicle formation (this evidence is supported by comparing Figure 10 panel c and panel f in [ 93 ] and in Figure 7a of [ 94 ]). Such a scenario is further supported by the finding that targeting the C-terminal domain of AHNAK1 (residues 5645–5673) to the membrane bound annexin2/S100A10 complex, in place of the full length AHNAK1, was sufficient to cause membrane blebbing that evolves into vesicular structures ( Figure 4 ).…”
Section: S100b Secretion By Adipocytesupporting
confidence: 63%
“…Dynamic S100B release into the blood and into the cerebrospinal fluid during acute brain injury may serve as a repair mechanism [ 98 ] but also contribute to neural disorders [ 37 ]. EVs are relevant carriers of both S100 proteins [ 99 ] and AHNAK [ 90 , 93 , 94 , 100 , 101 , 102 ]. Hence, an alternative pathway for S100B release into circulating fluids using EVs is plausible.…”
Section: S100b Secretion By Adipocytementioning
confidence: 99%
“…Amounts of protein in exosome were quantified using the BCA Protein Assay Kit (Takara Bio, Otsu, Japan). Transmission electron microscopy (TEM) analyses were performed by the Hanaichi Ultrastructure Research Institute (Okazaki, Japan) as previously reported [ 34 ]. The Nanoparticle Characterization System (NanoSight, Malvern Instruments, UK) was used to measure size distribution and concentration of exosomes.…”
Section: Methodsmentioning
confidence: 99%
“…IFN-α enhances TLR3-mediated antiviral activity by inducing protein kinase R (PKR) 25 . We previously reported that PKR in the dental pulp cell-derived microvesicles is critical as a powerful inducer of inflammation 26 . However, to our knowledge, no study has been published regarding the effects of IFN-α on MSC priming, and the effect of IFN-α in combination priming with TNF-α on the negative feedback loop of GMSCs remains unclear.…”
Section: Introductionmentioning
confidence: 99%